Collegiate Principal Structures in Implementing a School Behaviour Support Program: The Role of the Local Management Group Model. Issue 2 (13th December 2021) - Foggett, Judith; Conway, Robert; Dally, Kerry
Abstract: Student problem behaviour in schools is an issue for teachers, schools, and education jurisdictions. Problem behaviour also has an effect on families, the individual student, and the community. It is one of the principal issues of discussion for teachers, preservice teachers, principals, and policymakers. The purpose of this study was to examine a model that supports schools in managing available resources to promote positive behaviour and address problem behaviour. Interviews were conducted with 12 primary and high school principals to investigate their experiences of working together in 6 local management groups (LMGs) for the management of student behaviour. The findings revealed that the LMG model supported effective collaborative leadership practices between the high school and primary school principals and encouraged collegial networks among primary and high school teachers through joint professional learning opportunities. The benefits of the LMG model highlighted some positive outcomes for principals, teachers, and students with problem behaviour within their local schools.